Vertebrate ancient opsin photopigment spectra and the avian photoperiodic response. - Davies, W; Turton, M; Peirson, S; Follett, B; Halford, S; Garcia-Fernandez, J; Sharp, P; Hankins, M; Foster, R (2012)
In mammals, photoreception is restricted to cones, rods and a subset of retinal ganglion cells. By contrast, non-mammalian vertebrates possess many extraocular photoreceptors but in many cases the role of these photoreceptors and their underlying photopigments is unknown. In birds, deep brain photoreceptors have been shown to sense photic changes in daylength (photoperiod) and mediate seasonal reproduction. Nonetheless, the specific identity of the opsin photopigment 'sensor' involved has remained elusive. Previously, we showed that vertebrate ancient (VA) opsin is expressed in avian hypothalamic neurons and forms a photosensitive molecule. However, a direct functional link between VA opsin and the regulation of seasonal biology was absent. Here, we report the in vivo and in vitro absorption spectra (λ(max) = ~490 nm) for chicken VA photopigments. Furthermore, the spectral sensitivity of these photopigments match the peak absorbance of the avian photoperiodic response (λ(max) = 492 nm) and permits maximum photon capture within the restricted light environment of the hypothalamus. Such a correspondence argues strongly that VA opsin plays a key role in regulating seasonal reproduction in birds.